Audiovisual animation as an agent of social change: honoring our elders and the value of their life experience (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The animation project La vela (De Miguel, 2023) uses 2D animation to portray the life of an elderly man during COVID-19, reflecting on the digital exclusion faced by older generations. Inspired by the personal story of a grandfather and his granddaughter, the film highlights the isolation experienced during lockdown while promoting empathy and intergenerational connection. Methodologically, it is structured through a three-axis helical model linked to the project’s phases and to the academic profile that combines researcher and artist.
Keywords: Animation; elder people; COVID-19; experience; inquiry